Psoriasis complicated with arsenical keratosis and cutaneous squamous cell carcinoma: a case report - Liu, Qianwei; Chen, Bailin; Zhang, Jie (Frontiers in Oncology, 2024)
Rare cases of arsenical keratosis are attributed to the ingestion of arsenic-containing traditional Chinese medicines for conditions such as psoriasis. Arsenic is a potent carcinogen, and squamous cell carcinoma is known to develop in arsenical keratosis. A 51-year-old male patient with a 30-year history of psoriasis and a history of arsenic poisoning presented with suppuration, ulceration, and pain one and a half years after trauma to the right thumb. These symptoms had recurred after wound debridement, lesion resection, and pedicle flap transplantation. Histopathological examination of the skin lesions had suggested squamous cell carcinoma, and subsequent PET-CT examination had shown proliferation and enlargement of lymph nodes. Following right forearm amputation and radiofrequency ablation, additional lumps had been observed, but the patient had declined further surgery. Physical examination showed palpable enlarged axillary lymph nodes, which was confirmed by ultrasound. After three cycles of first-line immunotherapy with toripalimab combined with albumin paclitaxel and cisplatin chemotherapy, masses in the right upper arm were reduced. This case highlights the risks of arsenic-containing medicines used for treating psoriasis. Attention should be paid to the use of standardized treatments in psoriasis, as well as the probability of malignant transformation in arsenical keratosis.